Diterminasi Etika Profesional Auditor terhadap Kualitas Review Laporan Keuangan di Inspektorat Kabupaten Pinrang - Rahim, Syamsuri; Wahyuni, Nur; Nurhaswita, Nurhaswita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the professional ethics of auditors on the quality of financial report reviews at the Pinrang Regency Inspectorate. Data for this study were obtained using qualitative methods from employees of the Pinrang Regency Inspectorate in 2026, who agreed to participate as respondents. This study used primary data through direct field research, administering questionnaires/statement sheets to respondents, and using a census method. Due to the small sample size, the sample was the entire population, as the population consisted of only 37 auditors. Data analysis techniques were descriptive statistics and Partial Least Squares (PLS). The results showed that integrity had a positive and significant effect on financial report reviews. Objectivity had a positive and significant effect on financial report reviews. Competence had a positive and significant effect on financial report reviews. Auditor confidentiality had a positive and significant effect on financial report reviews. Professional behavior also had a positive and significant effect on financial report reviews. This indicates that the better the integrity, objectivity, competence, auditor confidentiality, and professional behavior of government internal supervisory officials, the better the quality of the resulting financial report reviews. Thus, these factors are essential elements in supporting an objective, professional, and standard-compliant financial report review process.